Virtual Reality in a Foreign Language Teaching - Renata Martini Kristo (Association of Social and Educational Innovation, 2017)
This article describes and elaborates on the educational potential of virtual reality, focusing on the use of three-dimensional environments in foreign languages teaching process. The study is concentrated on the analysis of one of the most used products recently, the virtual platform SECOND LIFE, by pointing out at potential possibilities that this platform offers to the didactic of foreign languages, but without leaving behind problems with which many users have to face during its implementation and use. In the introduction, the article focuses on the technology role in teaching in general and especially on foreign languages teaching. It continues on elaborating shortly on virtual reality, what it is, how it started, where it is used, and putting more emphasis on the use and possibilities it offers for the educational process and especially for foreign languages teaching.